A concentração sérica de tacrolimo após a ingestão de omeprazol: um estudo piloto - Peloso, Leonardo José (2014)
Introduction: Tacrolimus (TCR) is an immunosuppressant drug widely used in post-transplant organ recipients. Its absorption occurs principally in the duodenum and jejunum, its peak serum concentration is reached between 0.5 and 4 hours after ingestion (average 2 hours), and its absorption may be facilitated by an alkaline medium. Omeprazole (OMP) is a proton pump inhibitor in the parietal cells of the stomach that reaches maximum concentration between 0.5 and 3.5 hours after ingestion (average 2 hours), and because it reduces gastric acidity, it is capable of releasing more alkaline content into the duodenum. Pharmacological interactions between TCR and OMP are always described primarily with respect, to the common metabolic pathway (CYP3A4 and P-gp) used by both medications which may result in elevations of the TCR plasma concentration. The objectives of this study are to identify if there is an increase or decrease in the concentration of tacrolimus when administered after omeprazole and determine the frequency of subjects who increased in two hours, the bioavailability of tacrolimus after using omeprazole. Subjects and Methods: To that end, a double blind, placebo-controlled pilot study was performed in 28 post-renal transplant subjects regularly using TCR (mean: 0.08 ± 0.05 mg/kg/day BID) and OMP (20 mg/day MID). OMP or a placebo was ingested every morning at 6 am after fasting, and TCR was ingested 2 hours later at the doses reported above. Blood samples were taken 2 hours after the ingestion of TCR over 4 consecutive days under both the OMP and placebo regimes, being the subject the control same its. Serum concentrations of TCR were obtained using the chemiluminescent microparticle in human whole blood immunoassay method (CMIA, Abbott Lab., Brazil) after the subjects fasted for 3.5 hours. Results: Of the subjects evaluated, 18 (64.3%) were male, and 10 (35.7%) were female. In total, 8 (28.6%) of subjects received living donor kidneys, and 20 (71.4%) of subjects received cadaveric donor kidneys. The mean age of the subjects was 43 ± 13 years, and the average time since transplant was 41 ± 32 months. The mean serum creatinine and urea levels were 1.6 ± 0.5 mg/dL and 59 ± 27 mg/dL, respectively, and the mean hemoglobin level was 13.7 ± 1.9 g/dL. Conclusion: We found no significant difference in the mean serum TCR concentrations measured under the placebo or OMP regime (15.8 ± 8.7 ng/mL versus 15.7 ± 6.8 ng/mL, respectively, P=0.92). Compared with the placebo period, there was an increase in the serum TCR concentration greater than 10% in 13 subjects and greater than 20% in 10 subjects, which corresponded respectively, to 46.4% and 35.7% of the studied subjects. These data infer that OMP may increase the serum TCR concentration if ingested 2 hours before TCR ingestion, likely through alkalization of the intestinal contents. These frequency rates should be used to calculate the sample sizes needed for future studies with larger numbers of subjects.